2015
DOI: 10.1089/apc.2014.0205
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Predictors of Low Bone Mineral Density and Fragility Fractures Among HIV-Infected Patients at One Italian Center After Universal DXA Screening: Sensitivity and Specificity of Current Guidelines on Bone Mineral Density Management

Abstract: Low bone mineral density (BMD) is frequent in HIV infection regardless of the use of antiretroviral therapy (ART). Uncertainties remain, however, as to when in HIV infection BMD screening should be performed. We designed a prospective study to estimate the efficacy of universal BMD screening by dual-energy X-ray absorptiometry (DXA). Since April 2009 through March 2011, HIV patients attending our Center were offered femoral/lumbar DXA to screen BMD. Low BMD for chronological age, that is significant osteopenia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
10
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 48 publications
2
10
0
1
Order By: Relevance
“…Using their proposed strategy, which combines age, BMI and CD4+ T cell count, the sensitivity and specificity increased to 65% and 67%, respectively 26 . On the other hand, Mazzotta et al found in their cohort of 163 HIV+ adults (mean age 44, 71% men) that following the Italian DXA screening guideline for screening anyone with 2 risk factors other than HIV resulted in only a sensitivity of 32% and specificity of 81% for detecting a Z score≤−2.0 27 .…”
Section: Data On Fracture Risk Calculators In Hiv-infected Individualsmentioning
confidence: 96%
“…Using their proposed strategy, which combines age, BMI and CD4+ T cell count, the sensitivity and specificity increased to 65% and 67%, respectively 26 . On the other hand, Mazzotta et al found in their cohort of 163 HIV+ adults (mean age 44, 71% men) that following the Italian DXA screening guideline for screening anyone with 2 risk factors other than HIV resulted in only a sensitivity of 32% and specificity of 81% for detecting a Z score≤−2.0 27 .…”
Section: Data On Fracture Risk Calculators In Hiv-infected Individualsmentioning
confidence: 96%
“…Since this report, additional studies have continued to substantiate that low BMD is common in people living with HIV infection whether ART-treated[7*, 8*] or ART-naïve[9**, 10, 11]; and, in some[12**], but not all[13**, 14], comparative studies osteopenia and osteoporosis are more prevalent among HIV-infected individuals when compared with uninfected controls. Of greatest concern, however, are reports of heightened risk for fracture among people living with HIV.…”
Section: Introductionmentioning
confidence: 99%
“…An increase in the incidence of fractures in HIV + individuals was initially reported at the end of the last decade. Since then, several studies have described the incidence of fractures in people living with HIV (Table ) …”
Section: The Hidden Burden Of Fractures In Hiv‐positive Subjectsmentioning
confidence: 99%
“…The reported incidence of fractures at any skeletal site in people living with HIV ranges from 0.1 fractures per 1000 person‐years to 8.4 fractures per 1000 person‐years (Table ) . However, it is important to note that most of the studies were carried out in men with a mean age of between 36 and 56 years (Table ) . Men in this age group usually have a low frequency of fractures, so comparison with an age and sex‐matched population is important.…”
Section: The Hidden Burden Of Fractures In Hiv‐positive Subjectsmentioning
confidence: 99%
See 1 more Smart Citation